(untitled) (Scientific journal of the Fergana State University, 2024)
This article calls for the development of combat qualities in military leaders on the basis of the competence approach to become an urgent task at the level of demand. training camps, command-staff training exercises), which means the formation of the ability to use it in terms of military training, the development of various qualities necessary for the successful performance of these duties, The theoretical foundations of the methodology of combat qualities development were considered.